Language and culture pedagogy: From a national to a transnational paradigm - Risager, Karen (Languages for intercultural communication and education, 2007)
How can we envisage a new language and culture pedagogy that breaks with the tradition of viewing language as part of a closed national universe of culture, history, people and mentality, and begins to see itself as a field operating in a complex and dynamic world characterised by transnational flows of people, commodities and ideas? Initially, to understand the field and its current challenges, we must understand its history, and the first part of this book contains a critical analysis of the history of the international field of culture teaching – the first historical treatment of this field ever written. The next part of the book focuses on how we can build a framework for a new transnational language and culture pedagogy that aims at the education of world citizens whose intercultural competence includes critical multilingual and multicultural awareness in a global perspective.